Gone : Poems. - Howe, Fanny (New California poetry., 2003)
This collection of new poems by one of the most respected poets in the United States uses motifs of advance and recovery, doubt and conviction--in an emotional relation to the known world. Heralded as "one of our most vital, unclassifiable writers" by the Voice Literary Supplement, Fanny Howe has published more than twenty books and is the recipient of the Gold Medal for Poetry from the Commonwealth Club of California. In addition, her Selected Poems received the 2001 Lenore Marshall Poetry Prize for the Most Outstanding Book of Poetry Published in 2000 from the Academy of American Poets. The po.